Aplikasi Sistem Inventory Dengan Menggunakan Bahasa Pemrograman Mobile Pada CV. Multi Citra Kimia Cikarang (Studi Kasus CV. Multi Citra Kimia) - Sufajar Butsianto (Teknik Informatika, Universitas Pelita Bangsa, 2020)
The warehouse section of CV. Multi Citra Kimia sometimes has an error in conveying information about incoming data, outgoing goods and stock items because the data recording of goods is still using the manual method by writing in a notebook, ofcourse this method is less effective. Therefore, an application is needed to find out what items have entered and exited in order to facilitate the warehouse and secretary in informing the stock of goods to customers and directors effectively. The aim of this research is to find out ways for the warehouse to input goods data in a manner automatically with a barcode so that it does not hamper the sales process. The system method for this Android-basedapplication uses the prototype method. Making the software in this thesis, the authors use Sublime Text 3, Android Studio, and for the database using PhpMyAdmin. The result of making this application is inputting and checking stock information in and out of an android smartphone, by opening the inventory application on android then selecting the item input menu. To check the item, select the item stock menu containing items that have entered and exited using the system application. Testing of this application uses blackbox testing. This research shows that the inventory application system of this item can also use an Android-based Barcode scanner can make it easier for the warehouse to input goods data automatically, helping to facilitate the warehouse to convey information of goods data in and out to the secretary and director effectively. Keywords : Barcode, Android, Prototype, inventory, web.